2018
DOI: 10.1016/j.clinbiomech.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Bipedal hopping timed to a metronome to detect impairments in anticipatory motor control in people with mild multiple sclerosis

Abstract: This new timed hopping test may be able to detect both physical ability, and feed-forward anticipatory control impairments in people with mild MS. Hopping at a frequency of 40-bpm seemed more challenging. Several aspects of anticipatory motor control can be measured: including reaction time to the first metronome cue and the ability to adapt and anticipate the beat over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 187 publications
(352 reference statements)
0
3
0
Order By: Relevance
“…All other studies that investigated jumping in MS examined bipedal jumps. 21,23,24 Our study is the first to characterise single-leg jumps in MS.Our results suggest that pwMS-NM have significantly reduced SLCMJ performance compared to HC with the highest effect sizes for negative power and jump height. These results are consistent with Stagsted et al who showed that pwMS often Abbreviations: pwMS, people with Multiple Sclerosis, pwMS-RM, people with multiple sclerosis with reduce muscle strength, pwMS-NM, people with multiple sclerosis with normal muscle strength, HC, healthy controls, ND, non-dominant leg, D, dominant leg, LSI, Limb-Symmetry-Index, FZV, Force at Zero Velocity, FTCTR, Flight-Time-Contraction-Time Ratio.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…All other studies that investigated jumping in MS examined bipedal jumps. 21,23,24 Our study is the first to characterise single-leg jumps in MS.Our results suggest that pwMS-NM have significantly reduced SLCMJ performance compared to HC with the highest effect sizes for negative power and jump height. These results are consistent with Stagsted et al who showed that pwMS often Abbreviations: pwMS, people with Multiple Sclerosis, pwMS-RM, people with multiple sclerosis with reduce muscle strength, pwMS-NM, people with multiple sclerosis with normal muscle strength, HC, healthy controls, ND, non-dominant leg, D, dominant leg, LSI, Limb-Symmetry-Index, FZV, Force at Zero Velocity, FTCTR, Flight-Time-Contraction-Time Ratio.…”
Section: Discussionmentioning
confidence: 70%
“…19,21,22 Two pilot studies of Kirkland et al provide initial evidence that jumping, as a complex and innovative novel assessment tool in MS, can reveal differences between pwMS with mild disability and HCs, and is potentially useful for assessing lower limb neuromuscular function in pwMS. 21,23 In our previous pivotal study, we found that pwMS without any strength, coordination, and sensory impairments of the legs required more complex assessments, such as the countermovement jump (CMJ), a bipedal vertical jump, to identify neuromuscular deficits below the clinical threshold of EDSS. 24 The pwMS with full motor function showed significantly reduced CMJ performance in almost all observed kinetic, temporal, and performance parameters compared to the HC in this study.…”
Section: Introductionmentioning
confidence: 99%
“…This difference may be relevant as a change of 15% could be significant [48] and the fact that the control group walked at a high-intensity level controlled by rating perceived exertion. Nonetheless, the intervention group introduced this intensity by metabolic stress with the BFR intervention, and controlled the rests with a metronome, which may have produced better results at the brain level, especially anticipatory motor control [49]. In self-selected walking velocity (SSWV), both groups improved between 0.46 and 0.49 m per second, which may indicate that subjects with knee arthroscopy obtain the same benefits from BFR intervention and mechanical stimulus of the loads [43].…”
Section: Speedmentioning
confidence: 99%
“…To our knowledge, there are no studies that investigate CMJ performance in MS. Two pilot studies from Kirkland et al [ 21 , 22 ] provide the first evidence that jump tasks can detect differences between pwMS with mild disability and healthy controls and that they are a potentially useful measurement of lower limb function in pwMS. However, in contrast to our study, Kirkland et al assessed the use of horizontal jumps on an instrumental walkway system with small sample size.…”
Section: Introductionmentioning
confidence: 99%